An investigation into the effects of particle texture, water content and parallel plates׳ diameters on rheological behavior of fine sediment - Kashani, M.M.; Lai, S.H.; Ibrahim, S.; Sulaiman, N.M.N.; Fang, Y.T. (Elsevier, 2016)
Siltation, a phenomenon resulted from the presence of fine particles in an aqueous environment, dominated by silt and clay, is a known and common environmental issue worldwide. The accumulation of fine sediments engenders murky water with low oxygen levels, which leads to the death of aquatic life. Thus, investigating the physical and mechanical properties of fine sediment by rheological methods has expanded. Rheology is the science of deformation and flow of matter in stress. This survey investigates the rheological behavior of six samples of soil as the fine particles structure (D<63 µm) from different regions of Malaysia by using a rotational rheometer with a parallel-plate measuring (using two sizes: 25 mm and 50 mm) device to explore the flow and viscoelastic properties of fine particles. The samples were examined in two rheological curve and amplitude sweep test methods to investigate the effect of water content ratio, texture, and structure of particles on rheological properties. It was found that the content of fine sand, clay, and silt had an effect on the stiffness, structural stability, and shear behavior. Thus, the pseudoplastic and viscoelastic behavior are respectively shown. Moreover, the amount of fine sediments present in water i.e. the concentration of these particles, has a direct effect on the rheological curve. A reduction in viscosity of samples with higher concentrations of water has been observed. As a consequence, a considerable quantity of fine sediments are distributed within the water body and remain suspended over the time. As a result, the sedimentation rate slows down. It needs to be asserted that the storage modulus G′, loss modulus G″, and yield point can vary depending on particle type. The G′ and G″ were instigated for samples (70% and 45% concentrations) that demonstrated viscoelastic characteristics using the same rotational rheometer with a parallel-plate measuring device.